Self-Medication and its Determinants in Women of Reproductive Age in Gorgan city in 2018-2019 - Mohammad Shokrzadeh; Danial Jafari; Reza Hoseinpoor; Jafar Jalilian; Yaghoub Shayeste (Golestan University of Medical Sciences, 2020)
Background: Self-medication is an important concern for health authorities throughout the world. The women of reproductive ages were the most vulnerable groups at risk for self-medication in the society. The purpose of this study was to determine the frequency and some associated factors of self-medication in women of reproductive ages in Gorgan, north of Iran. Methods: This cross-sectional study was carried out on 800 women of reproductive age (15-49 years) who were residents in Gorgan, in 2018-2019. Data were collected through home visits and interviews using a checklist with 19 questions. Data were analyzed in SPSS-16 using Pearsonchr('39')s chi-squared test. Results: Self-medication was reported in 68.9% of reproductive ages. The majority of the self-medication was in the age range of 40-49 years (78.5%). The main cause for self-medication was found to be headache (68.6%) and common cold (57.7%). Most frequently, self-medication was related to pain killer drugs (90.6%) and NSAIDs (64.4%). Also, the major causes of self-medication were found to be the previous use experience (n=307) and availability of drugs at home (n=266). Finally, we found a significant association between self-medication with age, marital status, occupation, education, income, number of children and family size (p<0.05). Conclusions: Self-medication, mainly in pain-killer drugs and NSAIDs were high among women of reproductive age in Gorgan. Therefore, it seems necessary to provide public trainings for all women of reproductive age and train them about the dangers and side effects of self-medication.